A review of microplastic distribution in sediment profiles. (February 2021) - Uddin, Saif; Fowler, Scott W.; Uddin, Mohd. Faiz; Behbehani, Montaha; Naji, Abolfazl
Abstract: The growing use of plastic and their indiscriminate disposal into the environment has resulted in the accumulation of huge quantities of microplastic (MP) in the marine environment. Several studies have investigated the pathways of MPs reaching marine environments and a few have begun looking at their inventories in sediment profiles. Recent estimates suggest between 70 and 90% of the MP particles are accumulated into sediment profiles. This paper reviews MPs in sediment cores, and the methods used for chronological reconstruction to provide evidence to link the plastic usage and MP inventories over time. In one example, a 210 Pb dated sediment core from Kuwait Bay revealed 0.1 MPs g −1 of sediment deposited in approximately 1951 and 0.5 MPs g −1 in sediment from 2009 indicating a progressively increasing presence in recent sediments. The review also highlights the issue of very large spatio-temporal variation in MP concentrations, indicating the limitation of a snapshot study especially when dealing with the surface sediments; and it demonstrates the relevance of using sediment cores for a better assessment of MP input and inventories in the marine environment. It is proposed that MP sediment data should be reported as N m −2 year −1 or g m −2 year −1, and cores preferably dated using 210 Pb, and supported by at least one other stratigraphic marker to enhance the usefulness of these datasets, since 210 Pb can reliably date sediments as old as 100 years, a time-span which extends well beyond the time plastic production began. The anomalies in data processing and reporting in terms of number per kg of sediment or per cm 2 /m 2 should be addressed essentially by adopting a standardized protocol. Highlights: Sediment cores are more reliable than surface sediments for assessing MP inventories. Sediment dating techniques for reconstruction of MP inputs need standardization. MPs analyzed in first 210 Pb-dated sediment core from Kuwait MP abundance decreases with depth in the sediment cores. Temporal changes of MP in cores require 210 Pb dating to obtain verifiable data.